Studying the Glycogen Synthase Kinase 3β and Arrestin β-1 Levels in Patients with Metabolic Disorders - Mohammed, Asmaa; Khaleel, Fayhaa M. (Iraqi Journal of Science, 2026)
Metabolic disorders, characterized by concurrent metabolic abnormalities such as dyslipidemia, hyperglycemia, and obesity, involve dysregulated signaling pathways critical to energy homeostasis. This study investigates the interplay between the Glycogen Synthase Kinase 3β (GSK3β) enzyme and the protein Arrestinβ-1in individuals with metabolic disorders. A total of 135 samples were collected and divided into 2 groups: The first group was the controls, n= 46, and the second group the patients, which was divided into two groups:  45 patients with metabolic disorders patients (dyslipidemia, hyperglycemia, and obesity), and 44(T2DM) patients with obesity, Samples were collected from AL-Yarmouk Teaching Hospital from August to September 2024. Biochemical variables were assessed in all sample groups, including the quantification of GSK3β, Arrestinβ-1, and insulin by the ELISA technique . Glycemic and lipid profiles were measured. The findings indicated elevated GSK3β and Arrestin β-1 levels in the obese  T2DM when compared with the control group. The statistical analysis showed a favorable association between insulin resistance andGSK3β and Arrestinβ-1. This study demonstrates that both GSK3β enzyme and Arrestin β-1 serve as effective biomarkers for predicting metabolic disorders. Their critical roles in metabolic disorders lead them to the development of these metabolic pathways. Disruptions in this signalling pathway result in beta cell damage which is one of the causes of diabetes, which is considered one of the Risk factors of metabolic disorders in addition to obesity and dyslipidemia.